Results of the prospective observation in routine practice of hypertensive patients with concomitant chronic respiratory diseases. Part II. Predictors of adverse events - M. I. Smirnova; V. M. Gorbunov; A. S. Kurekhyan; G. F. Andreeva; Ya. N. Koshelyaevskaya; А. D. Deev (Кардиоваскулярная терапия и профилактика)
Aim. To study the predictors of adverse events in hypertensive (HTN) patients, including those with chronic respiratory diseases (CRDs).Material and methods. Regression analysis evaluated clinical and anamnestic data and blood pressure (BP) in outpatients with stage II-III HTN (n=156): 49 patients had asthma, 20 — chronic obstructive pulmonary disease; age — 63,4±8,8 years, women — 72,4%, followup duration 29,3±8,0 months. The outcomes included in the composite primary endpoint (EP) were registered in 32 patients (death, major cardiovascular events and complications), while the secondary EPs were registered in 57 patients (hospitalizations, emergency calls, temporary disability due to cardiovascular disease/CRD, hypertensive crisis, exacerbation of CRD, pneumonia, respiratory failure), and tertiary EP — in 76 (other significant diseases/conditions, including increased blood pressure without hypertensive crisis, requiring correction of regular therapy).Results. Predictors of primary EPs were the decrease level of nocturnal diastolic BP (DBP) (β=-5,335, p=0,026), nocturnal DBP variability (β=1,796, p=0,007), blood leukocyte level (β=0,241, p=0,039); secondary EPs — systolic blood pressure ≥170 mm Hg in history (β=1,305-1,641, p=0,037-0,017), statin use (β=-0,997, p=0,037), CRD (β=0,734, p=0,023), blood platelet level (β=-0,008, p=0,022); tertiary EPs — only CRD (β=1,082, p<0,0001).Conclusion. Patients with HTN need complex multifactorial prevention. It is necessary to improve the control of office and ambulatory blood pressure, blood lipids, especially in the presence of CRD, to improve the control of CRDs themselves. The method of 24-hour blood pressure monitoring should be used more often in routine practice, including assessing the degree of nocturnal blood pressure reduction and its variability.